Analysis Of The Implementation Of Standard Operating Procedures (SOP) In The Administration Division At PT Rezeki Surya Intimakmur (PT RSI) - Abel Armanda Putra; Muhammad Bakr Muhlison (International Journal of Economics, Business and Innovation Research, 2024)
This research was conducted alongside the internship program at PT Rezeki Surya Intimakmur (PT RSI) from March 1, 2023, to June 31, 2023. The purpose of this research is to analyze the implementation of Standard Operating Procedures (SOP) at PT RSI. The research focuses on the administrative division, which handles the maintenance project for air conditioners and generators at Starbucks. PT RSI is a contracting company that collaborates with both national and international companies. Therefore, PT RSI must maintain its credibility by consistently adhering to proper SOPs. This research uses the theory from Santosa's book entitled "Understanding S.O.P. (Standard Operating Procedure)" which focuses on the seven key aspects of SOP as a reference for the study. A qualitative approach was used in this research, with in-depth interviews conducted with the interviewees. The interviews were conducted to gain a deep understanding of SOP implementation. The research involved two employees from the administrative division at PT RSI. The results show that the implementation of SOPs in the administrative division at PT RSI has been running quite well. There have been no critical errors made by employees toward clients. PT RSI has fulfilled the seven key aspects of SOP within their company. The only challenge lies in the working hours of employees who are not always available to address client complaints beyond regular working hours. This issue can be resolved by addressing client complaints the following day or during regular working hours.